Micromechanisms of Cortical Bone Failure under Different Loading Conditions - Sharma, N. K.; Sharma, Swati; Rathi, Apoorv; Kumar, Abhinav; Saini, Karan Vir; Sarker, M. D.; Naghieh, Saman; Ning, Liqun; Chen, Xiongbiao (Journal of Biomechanical Engineering-Transactions of the Asme, 2020)
Bone being a hierarchical composite material has a structure varying from macro- to nanoscale. The arrangement of the components of bone material and the bonding between fibers and matrix gives rise to its unique material properties. In this study, the micromechanisms of cortical bone failure were examined under different loading conditions using scanning electron microscopy. The experimental tests were conducted in longitudinal and transverse directions of bone diaphysis under tensile as well as compressive loading. The results show that bone material has maximum stiffness under longitudinal tensile loading, while the strength is higher under transverse compressive loading. A reverse trend of compressive mechanical properties of bone is observed for longitudinal and transverse loading as compared to trends reported in the previous studies. Therefore, micromechanisms of cortical bone failure were analyzed for different loading conditions to reveal such type of behavior of cortical bone and to correlate bone microstructure with mechanical response of bone.
CRIS-Team Scopus Importer:2020-08-28
Keywords: bone; compressive loading; micromechanism; SEM; tensile loading